Influence of Anisotropy on the Swelling Properties of Alentejo Flysch Rocks (Portugal) - Pinho, António B. (2020)
This paper aims to contribute to the knowledge of the swelling properties for the rock materials belonging to the Baixo Alentejo Flysch Group (BAF) in the south of Portugal. These formations are flysch-type deposits constituted by sequences of usually thick greywacke beds alternating with thin soft shale beds, which include sometimes intercalations of conglomerate beds. All the sedimentation of these flysch formations was controlled by tectonics. At the same time, should have occurred along with the first Hercynian deformation phase, a low-grade metamorphic event (chlorite zone), that affected these flysch deposits. The geotechnical characterization is a difficult task, mainly in shales, due to the anisotropy and heterogeneity of these rock materials. The anisotropy verified in some properties is caused by foliation, which besides making the sample preparation difficult to the laboratory tests, it also gives rise to a scattering of the measured properties values, as for example, the swelling, the strength and the deformability. The heterogeneity is related to the typical characteristics of the BAF flysch formations, where thinly stratified greywacke and soft shale beds are common, which sometimes may affect the laboratory tests results making them less representative. The heterogeneity and anisotropy revealed in the rocks of BAF, are also verified at rock mass scale. The rock masses of BAF are characterized by a great structural complexity, with intense folding and shearing, that affects the flysch formations with alternation of shales and greywackes beds with distinct mechanical properties. As a result of its complex structure, the rock masses of BAF present a weathering zone with irregular boundaries, sometimes several metres unlevelled between the fresh to slightly weathered rock mass and the highly to completely weathered rock mass constituted by soft rocks and residual soils. In this study, an attempt is made to evaluate the swelling properties of these flysch rocks, mainly of the soft shales, in what concerns to the assessment of the influence of anisotropy on the swelling behaviour of these rock materials.